(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2019)
Creativity, divine gift for people who brought it innate, considered as a set of traits that each individual possessed. At present it is proven that all have the ability to be creative or to depart from the usual thought patterns and behaviors with originality, flexibility, feasibility, fluidity and elaboration. This quality can decrease according to the environment in which people develop, either by their actions, interests and ideas that transform the life of each one. This reason motivated the authors to do the work that aims at developing creativity in third-year students of Primary Education, In-service Course modality, for their performance on the practice of their profession. From indicators consulted, indicators for the stimulation and development of creativityare offered.